Stakeholder Analysis In The Strategic Development Planning Of Batutulis Tourism Area, Bogor City - Bambang Hengky Rainanto; Fitria Herawati; Siti Yasmin Salsabila Sunantoputri; Charles Parnauli Saragi; Abdul Thalib Bon; Jonathan Van Melle; Bambang Rudyanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Bogor, one of Indonesia's oldest cities, is renowned for its distinctive culture and rich historical heritage, including the Batutulis area. This area holds significant remnants of the Sundanese Kingdom's history and has been designated as a historical and cultural tourism destination in Bogor. Effective development of a tourism area necessitates collaboration among various stakeholders. However, in the case of Batutulis, insufficient communication and cooperation have led to misunderstandings among stakeholders. To address these issues, appropriate strategies are essential in the non-physical planning of the Batutulis Tourism Area, including stakeholder roles, tourism product development, and marketing strategies to ensure comprehensive and well-structured tourism planning. This research aims to identify, classify, and analyze the relationships between stakeholders involved in developing the Batutulis Tourism Area. A descriptive qualitative method was employed, integrating stakeholder and SWOT analyses. Data collection techniques included observations, interviews, and document reviews, with interviews conducted with stakeholders identified through the Pentahelix Strategy. The successful development of the Batutulis Tourism Area depends on strategic planning and collaboration among stakeholders, emphasizing the need for synergy in coordination, communication, and cooperation. Keywords: Stakeholders, Pentahelix Strategy, Non-Physical Planning, Tourism Development, Historical and Cultural Tourism